Clinical Outcomes of Patients With Anterior Shoulder Instability and Glenolabral Articular Disruption Lesions: A Retrospective Comparative Study. Issue 14 (December 2020) - Davey, Martin S.; Hurley, Eoghan T.; Colasanti, Christopher A.; Scanlon, John P.; Gaafar, Mohamed; Hogan, Brian A.; Pauzenberger, Leo; Mullett, Hannan
Background: Anterior shoulder instability is a common clinical condition that often requires surgical stabilization. Glenoid labral tears are often associated with instability, with glenolabral articular disruption (GLAD) lesions occasionally being identified arthroscopically during repair, particularly in collision athletes. Purpose: To evaluate the clinical outcomes and recurrence rates in patients who had GLAD lesions and underwent arthroscopic Bankart repair (ABR) and compare them with a control group without GLAD lesions. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective review of patients who underwent ABR with GLAD lesions, by a single surgeon between July 2012 and March 2017, was performed. Additionally, these were pair matched in a 2:1 ratio for age, sex, sport, and level of play with a control group who underwent ABR without GLAD lesions. Return to sport, the level of return, and the timing of return were assessed. The visual analog scale (VAS) for pain score, Rowe score, Shoulder Instability–Return to Sport after Injury (SIRSI) score, and Subjective Shoulder Value (SSV) were evaluated. Results: The study included a total of 66 patients (22 and 44 patients for the GLAD and control groups, respectively), with a mean age of 25.8 years and a mean follow-up of 66 months. Overall, there was no significant difference in any of the clinical outcome scores (VAS, Rowe, SIRSI, and SSV) utilized for the GLAD and control groups ( P > .05 for all). Similarly, there was no significant difference in the total rate of return to play (90.9% vs 88.6%; P > .99) or return at the same/higher level (68.2% vs 72.7%; P = .78). There was no significant difference in timing of return to play (6.3 ± 6.6 months vs 6.4 ± 2.5 months; P = .98). There were 3 cases (13.6%) requiring further surgery (1 revision stabilization, 1 arthroscopic release, and 1 rotator cuff repair) in the GLAD group and 2 cases (4.5%) requiring further surgery (both revision stabilization) in the control group; the difference was not statistically significant ( P = .32). Conclusion: After arthroscopic repair, patients with GLAD lesions had similar midterm outcomes when compared with a control group without GLAD lesions.